Effect of Infrared in the Natural Immune Response in White Mice injected with Radiated protoscoleces of Echinococcus granulosus - Suhaila Yousef; Hanan Saadoun (College of Education for Pure Sciences, 2012)
Abstract The present study investigated the effect of infrared irradiation in the immune response of BALB/c mice against infection with secondary hydatid disease. By exposing protoscoleces of Echinococcus granulosus to infrared radiation at the periods 1, 2, 3, and 5 minutes, 20 cm from the light source, at wave length of 700-750 nm. Irradiated protoscoleces were injected in mice intraperitoneally. Many criteria were taken into consideration, 3, 15, and 30 days post injection, including WBCs total and differential count, innate immunity represented by phagocytosis, in comparison with the control group (mice infected with non irradiated protoscoleces). The study revealed a significant increase (P≤0.001) in the WBCs total count in mice injected with irradiated protoscoleces, in comparison with the control group. Regarding to the WBCs differential count, a significant increase (P≤0.05) in the lymphocytes 3 days post injection was noticed, followed by increase 15 days post injection, which was persisted significantly (P≤0.05) 30 days post injection. A significant increase (P≤0.05) in neutrophils and monocytes was noticed in treated mice at all irradiation periods. A significant increase (P≤0.001) in the mean of phagocytosis in treated mice was reported, at all irradiation periods. It will be concluded that irradiation may be used as an immunostimulator against injection with secondary hydatid disease in mice.